Legal Barriers and Re-Victimization for Survivors of Intimate Partner Violence Navigating Courts in Utah, United States - Gezinski, Lindsay B. (Women & criminal justice, 2022)
Even though the majority of intimate partner violence (IPV) incidents remain unreported and unprosecuted, survivors find themselves navigating the legal system. One hundred and two survivors and service providers participated in semi-structured focus groups or interviews related to their IPV-related court experiences. Data analysis consisted of identifying themes, coding categories, and developing matrices. Themes included: (1) insufficient legal representation, (2) protection order access and enforcement, (3) revictimization in court settings, and (4) disparities in accountability. Participants pointed to a failure to enforce protection orders, mandated child visitation with perpetrators, and lenient sentencing as evidence that the legal system favors perpetrators. Findings indicate the need for IPV education for court personnel, as well as the expansion of public assistance and pro bono legal services.